Introduction to the second issue of JALT (Journal of Applied Learning and Teaching, 2018)
While history tells us that it is nothing new when both leaders of nations and captains of industry blatantly lie, one would have thought that the Internet makes fact-checking easier for all. However, in an era of data inflation, many appear to miss the forest for the trees, with populist backlashes across continents and conspiracy theories abounding. Amongst much other pseudoscience, perhaps most unbelievably and a quintessential sign of the times, there are substantial ‘flat Earth’ societies – as if we would not have the ability to photograph our blue planet from outer space and as if there had never been a Galileo Galilei some 400 years ago!